Ruta aviturística en el Cantón Pujilí. - Cola Chilig, Dennis Israel (2022)
Ecuador is one of the countries with the greatest biodiversity worldwide, which positions it as an important destination for avituristic activities, however, in the Pujilí canton, the use of bird biodiversity cannot be evidenced due to lack of knowledge of the local population in terms of the benefits of avituristic activities.The present research study had the objective of designing an avitouristic route in the canton of Pujilí, in which different parishes of the canton were integrated, offering an economic alternative to the population that will benefit from the creation of them. In this way, a diagnosis of the study area was proposed, through the bibliographic review, the conditions of the canton were established with their respective characteristics such as the different climatic floors that the canton possesses, which gives way to a great variety of bird species. On the other hand, twelve natural attractions with greater natural wealth were identified to establish the definitive observation points. Then, the need to carry out an inventory of species through field trips was established, applying the methodology of direct observation, point counting and intensive search, and then proceeding to identify the species through tools such as the bird book of Ecuador, bird websites like E-Bird and Bioweb of the Pontificia Universidad Católica del Ecuador, in total, 55 species were registered in the taxonomic files that consist of their scientific name, English name, common name and their vulnerability, it is crucial to mention that most birds are in a state of minor concern and two species in a state of vulnerability. For the selection of the definitive observation points, a discrimination table was made, in which important factors were taken into account such as the tourist plant, the condition of the roads and their accessibility, moreover, the Sorensen index was applied to get a better understanding of the similarity of the species at the different sighting points. Hence, it was possible to develop the definitive route, which consists of five sighting zones, in a distance of 170 km, taking into account that the starting point is from the city of Latacunga. Also, the tours were planned in two tours, a full day and two days one night. Finally, it is expected that the route can be used by the local people and the sectors surrounding the different points, to promote tourist and avituristic activities, so economic income and environmental conservation will be boosted.